Constraints on the accumulation of organic matter in Upper Ordovician-lower Silurian black shales from the Lower Yangtze region, South China. (October 2020) - Yang, Shengchao; Hu, Wenxuan; Yao, Suping; Wang, Xiaolin; He, Weihui; Wang, Yin; Zhu, Feng; Sun, Funing
Abstract: The Late Ordovician to early Silurian (O/S) was an important period in which many significant geological events occurred. During the O/S transition, organic-rich black shales were widely deposited and became important unconventional energy sources. Paleoproductivity, detrital input, and redox conditions are the three major factors controlling organic matter (OM) accumulation. Although the effect of each factor is relatively clear, the complex influences of these factors remain poorly understood. Specifically, the evolution of these factors and the corresponding influence on the accumulation of OM during the O/S transition has not yet been systematically investigated. This paper investigates the constraints on OM accumulation in O/S transition black shales from the Lower Yangtze region, based on graptolite fossil identification, zircon U–Pb dating, and geochemical analyses of a well sequenced drilling profile. The results show that (i) the SY-1 core sequence was well constrained from graptolite zones WF2 (447.62 Ma) to LM5 (441.57 Ma) across the O/S boundary, with decreasing sedimentation rates (SRs) in the upper Katian (WF2 to WF3) and increasing SRs in the lower Rhuddanian; (ii) complementary volcanic inputs (Katian and Rhuddanian) and upwelling events (Hirnantian) exerted strong control over paleoproductivity; (iii) orogenic processes in South China controlled detrital inputs and redox conditions; (iv) OM accumulation in the Lower Yangtze area across the O/S transition occurred in three stages. In stage 1 (WF2–WF3), strong volcanism boosted productivity, whereas OM preservation was not favored in the oxic environment. In stage 2 (WF4–LM3), upwelling and volcanism resulted in high productivity and provided the optimal configurations for OM enrichment. In stage 3 (LM4 and later), rare OM was preserved due to terrestrial dilution and unfavorable preservation conditions. Eventually, WF4–LM3 became the prominent OM-rich biozones due to the effective coordination of the controlling factors, namely upwelling, volcanism, and redox conditions. Highlights: Zircon dating and graptolite fossils constrain the drill core to WF2–LM5 across the O/S. Productivity was jointly affected by complementary volcanic inputs and upwelling. Detrital flux and redox conditions were controlled by the orogeny process in South China. Three different patterns were established for organic matter accumulation across the O/S.